2012
DOI: 10.1155/2012/271589
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary Behavior and Physical Function Decline in Older Women: Findings from the Women's Health Initiative

Abstract: Sedentary behavior is associated with deleterious health outcomes. This study evaluated the association between sedentary time and physical function among postmenopausal women in the Women's Health Initiative Observational Study. Data for this prospective cohort study were collected between 1993–1998 (enrollment) and 2009, with an average of 12.3 follow-up years. Analyses included 61,609 women (aged 50–79 years at baseline). Sedentary time was estimated by questionnaire; physical function was measured using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
116
4
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(141 citation statements)
references
References 27 publications
6
116
4
12
Order By: Relevance
“…In recent years, a number of cross-sectional and prospective studies have reported that higher levels of self-reported or objectively measured sedentary behaviours are associated with reduced muscle strength and poorer functional performance in older adults, independent of physical activity [16,18,19,40,44]. For instance, the findings from the Women's Health Initiative Study involving 61,609 postmenopausal women followed for an average of 12.3 years showed that those who reported >8-11 and >11 h/day of sedentary time had lower physical function (using the RAND SF-36 scale) between baseline and follow-up compared to those reporting ≤6 h/day [44].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a number of cross-sectional and prospective studies have reported that higher levels of self-reported or objectively measured sedentary behaviours are associated with reduced muscle strength and poorer functional performance in older adults, independent of physical activity [16,18,19,40,44]. For instance, the findings from the Women's Health Initiative Study involving 61,609 postmenopausal women followed for an average of 12.3 years showed that those who reported >8-11 and >11 h/day of sedentary time had lower physical function (using the RAND SF-36 scale) between baseline and follow-up compared to those reporting ≤6 h/day [44].…”
Section: Discussionmentioning
confidence: 99%
“…Our primary outcome of interest was changes in objectively measured sedentary behavior using accelerometers; given our focus on sedentary adults, and the fact that exchanging sedentary for even light activity is known to have physiological and psychological benefits (17)(18)(19)(20), we focused on the proportion of each day that participants were sedentary. More specifically, we collected accelerometer data during a baseline measurement week and for 1 mo following the intervention (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, sedentary behavior increases risk, independent of other types of activity, and exchanging sedentary for even light activity has physiological and psychological benefits (17)(18)(19)(20)(21)(22)(23). However, sedentary lifestyle is still prevalent despite worldwide efforts to increase activity; according to the World Health Organization, "60% to 85% of people in the worldfrom both developed and developing countries-lead sedentary lifestyles" (24).…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] However, even among people who engage in periods of purposeful exercise, sedentary behaviours can increase the risk of adverse outcomes, such as metabolic risk factors, functional limitations, and all-cause and cardiovascular disease mortality. [10][11][12][13][14][15][16] Even so, a recent meta-analysis showed that engaging in moderate physical activity, such as exercise, for at least 1 hour/day could eliminate the detrimental effects of prolonged sitting. …”
mentioning
confidence: 99%